ANALYZING DIFFERENT READINGS OF THE WORD LÄ€MASTUM AND INVESTIGATING ITS IMPACT ON INTERPRETATIVE PERCEPTIONS AND ENGLISH TRANSLATIONS - Askari, Seyed Kamel; Mousavi, Seyed Mohsen; Hasani, Seyed Mohamad (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2024)
This article discusses the difference in the reading of the word LÄmastum QS. Al-Nisa': verse 43. It has resulted in the formation of two meanings; Shafi'i chose the recitation of Lamastum and stated that touching women invalidates ablution, Hanafi accepted the recitation of LÄmastum and declared that touching women does not invalidate ablution. Others have opinions for and against these two views. This research, which has been carried out in an analytic-descriptive method, has examined the difference in the readings of the word LÄmastum in this verse. The results of this study show that the difference in the reading of LÄmastum-Lamastum does not lead to a difference in meaning, but what causes different jurisprudential views of this verse is paying no attention to the ironical meaning and misunderstanding of the interpretation, which ultimately caused some translators suffice for the literal meaning and did not consider the ironic meaning of the word, and therefore, some English translators of the Holy Qur'an are not immune to this mistake.